2014
DOI: 10.1111/febs.12670
|View full text |Cite
|
Sign up to set email alerts
|

Specific loop modifications of the thrombin‐binding aptamer trigger the formation of parallel structures

Abstract: Guanine-rich sequences show large structural variability, with folds ranging from duplex to triplex and quadruplex helices. Quadruplexes are polymorphic, and can show multiple stoichiometries, parallel and antiparallel strand alignments, and different topological arrangements. We analyze here the equilibrium between intramolecular antiparallel and intermolecular parallel G-quadruplexes in the thrombin-binding aptamer (TBA) sequence. Our theoretical and experimental studies demonstrate that an apparently simple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 65 publications
2
11
0
Order By: Relevance
“…These data indicated that the presence of the dye induced the shift of the TBA folding from a monomolecular- to multimeric- Q. In line with these results, previously reported studies have demonstrated the sensitivity of the TBA-Q typology to such specific modifications [ 62 ]. In order to obtain additional information about the structural features of the 5′-DMAzo-TBA-Qs fluorescence experiments were also performed irradiating at 255 nm the 5′-DMAzo-TBA or TBA in both the 100 K buffer and 5KEW.…”
Section: Discussionsupporting
confidence: 84%
“…These data indicated that the presence of the dye induced the shift of the TBA folding from a monomolecular- to multimeric- Q. In line with these results, previously reported studies have demonstrated the sensitivity of the TBA-Q typology to such specific modifications [ 62 ]. In order to obtain additional information about the structural features of the 5′-DMAzo-TBA-Qs fluorescence experiments were also performed irradiating at 255 nm the 5′-DMAzo-TBA or TBA in both the 100 K buffer and 5KEW.…”
Section: Discussionsupporting
confidence: 84%
“…Less is known about clusters of natural lesions in non-canonical, unusual DNA and RNA structures, such as the G-quadruplex which is currently the most comprehensively studied non-B model (18). Regarding G-quadruplex modifications that can be defined retroactively as clustered modifications, multiple mutations by natural and synthetic bases of the guanines in the G-tetrads as well as of the bases in loops should be mentioned (1924). In this study, we only deal with clustered natural lesions in quadruplexes.…”
Section: Introductionmentioning
confidence: 99%
“…Gel Electrophoresis. Since some authors have shown that site-specific changes in the TBA sequence can result in the formation of bimolecular structures [17], before further investigations, ODNs H1, H2, and H3 have been analyzed by PAGE, in which the TBA has been used as a reference (Figure 2). As it is evident from the electropherogram, all the three investigated heterochiral ODNs show a main band with electrophoretic motilities very similar to TBA, thus strongly suggesting the occurrence of major monomolecular G-quadruplex structures resembling the TBA chair-like Gquadruplex.…”
Section: Resultsmentioning
confidence: 99%